Aplasia Cutis Congenita: An Often Isolated Clinical Finding - Cátia Martins; Raquel S. Gonçalves; Joana Xará; Mariana Batista; Rita Carvalho; Rui Castelo (Gazeta Médica, 2023)
Aplasia cutis congenita (ACC) is a rare congenital condition characterised by the absence of skin, with or without the absence of underlying structures. Can appear as an isolated lesion or associated with other congenital malformations. The approach can be conservative or surgical. We report a case of a full-term male newborn with two adjacent ulcerated lesions with well-demarcated limits in the upper occipital region (20 and 4-5 mm diameter). Other alterations that could be associated with aplasia cutis were identified at examination, so the patient was referred to several consultations, and other system involvement was excluded. Re-evaluation at the first month of life revealed complete healing and conservative treatment was kept. After identification of ACC should be excluded other associated congenital malformations. Particularly if large skin defects or bone involvement is detected (higher risk of complications and mortality).